Crazy rich Asians a semiotic analysis on Asian and Asian-American identity representation on western media - Tigon, Joshlyn Joy R.; Piala, Julius Neil A. (2019)
Crazy rich Asians, a 2018 released movie adaptation of the New York Times best-selling book by Kevin Kwan which earned 26.5 million dollars in the US box office on its first week., has gained the spotlight for being the second movie having an all Asian cast on the big screen, 25 years after the first produced all Asian cast Hollywood film, The Joy Luck Club in 1993. The said film has been deemed the beacon of representation in Western media by movie critics for countering the stereotypes of Asian and Asian-American identity. This thesis explored how the identity of Asians and Asian-Americans is represented in the recently released film Crazy Rich Asians and how the said representation consists the predominant themes of stereotypes of Asian and Asian-American in the Western media, specifically looking into 1) how Asian and Asian-American identity is represented in the film through semiotics employed in the film, 2) the different representations of Asian and Asian-American identity in the film and how do those reflect predominant Asian and Asian-American stereotypes and themes in Western media, 3) the implications of the identified representations conveyed in the film towards the Asian and Asian-American identity, 4) the signs employed in the film that constructed and conveyed representations of Asian and Asian-American identity and the manner how these signs were employed, and 5) the decoded meaning from the identified signs and how those meanings convey Asian and Asian-American identity and reflect Asian and Asian-American stereotypes. Results show that Robert Lee?s Six faces f Orientals are still reflected and utilized as predominant Asian and Asian-American representations in Western media.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019